Parenting styles and bullying in an Ecuadorian educational unit - Alcivar-Morales, Rosa Melissa (2025)
What is the relationship between parenting styles and bullying in an Ecuadorian educational unit? 123 adolescents between the ages of 12 and 15 participated, who were in the 8th to 10th year of higher basic education. Quantitative, observational and correlational research. Use of two instruments: Perception of Parenting Styles Questionnaire and Bullying and School Violence Scale. The medium level predominated in most parenting styles (between 49.6 and 82.9%); as well as the category not found in the data related to bullying (between 47.2 and 74.8%). There was a significant correlation (p<0.05), directly proportional and with a weak to moderate intensity (Rho from 0.193 to 0.351) of the hostile parenting style in both parents with bullying.